МОДЕЛІ, ЗАСОБИ ТА ЗАХОДИ ЗАБЕЗПЕЧЕННЯ НАДІЙНОГО ТА ЕФЕКТИВНОГО ФУНКЦІОНУВАННЯ ЕНЕРГОПОСТАЧАЛЬНИХ КОМПАНІЙ, БАЛАНСУВАННЯ ТА РОЗПОДІЛУ ЕЛЕКТРОЕНЕРГІЇ В ОЕС УКРАЇНИ - Кириленко, О.В.; Буткевич, О.Ф.; Черненко, П.О.; Блінов, І.В. (Інститут електродинаміки Національної академії наук України, 2019)
The main results execution of scientific tasks of the Target Complex Program of Scientific Researches of the National Academy of Science of Ukraine "Scientific and technical bases of energy cooperation between Ukraine and the European Union" (Association-3) obtained in the department No 3 of the Institute of Electrodynamics of the National Academy of Sciences of Ukraine are shortly presented. References 8, figures 2, table 1.